2012
DOI: 10.1007/s12471-012-0284-8
|View full text |Cite
|
Sign up to set email alerts
|

Design and methodology of the COACH-2 (Comparative study on guideline adherence and patient compliance in heart failure patients) study: HF clinics versus primary care in stable patients on optimal therapy

Abstract: Background Since the number of heart failure (HF) patients is still growing and long-term treatment of HF patients is necessary, it is important to initiate effective ways for structural involvement of primary care services in HF management programs. However, evidence on whether and when patients can be referred back to be managed in primary care is lacking. Aim To determine whether long-term patient management in primary care, after initial optimisation of pharmacological and non-pharmacological treatment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Risk stratification and identification of these patients who are likely to decompensate remain an inexact science with fears of discharging optimised patients to general practice deterring those in secondary and tertiary care from this option. Recent results from the NorthStar [26] and COACH-2 [27] trials have, however, indicated that stable patients who are pharmacologically optimised may indeed be safe to 'graduate' to primary care follow-up. With previous disappointing results using the natriuretic peptides, questions remain as to how best to monitor such individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Risk stratification and identification of these patients who are likely to decompensate remain an inexact science with fears of discharging optimised patients to general practice deterring those in secondary and tertiary care from this option. Recent results from the NorthStar [26] and COACH-2 [27] trials have, however, indicated that stable patients who are pharmacologically optimised may indeed be safe to 'graduate' to primary care follow-up. With previous disappointing results using the natriuretic peptides, questions remain as to how best to monitor such individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This may, however, cause organisational and/or communicational uncertainties in daily practice. 17 , 18 , 20 , 23 , 24 , 40 42 …”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 In addition to healthcare providers, patient involvement is an important part of DMPs. 12 , 19 , 20 However, DMPs are not uniformly implemented in Europe. In part, this may be related to the fact that DMPs do not refer to one single, clearly defined programme, but to an overall concept of delivering care.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our understanding of the exact mechanisms of progressive intolerance to exercise is far from complete. Failure of inotropic and vasodilatory agents to improve exercise capacity implies that cardiac dysfunction is not the only factor contributing to progressive exercise intolerance [4]; impaired pulmonary and skeletal muscle function are also thought to have a role [5,6].…”
Section: Introductionmentioning
confidence: 99%